Alpha-Herpesvirus Thymidine Kinase Genes Mediate Viral Virulence and Are Potential Therapeutic Targets - Xie, Ying; Wu, Liping; Wang, Mingshu; Cheng, Anchun; Yang, Qiao; Wu, Ying; Jia, Renyong; Zhu, Dekang; Zhao, XinXin; Chen, Shun; Liu, Mafeng; Zhang, Shaqiu; et al. (Frontiers in Microbiology, 2019)
α-herpesvirus thymidine kinase (TK) genes are virulence-related genes and are non-essential for viral replication; they are often preferred target genes for the construction of gene-deleted attenuated vaccines and genetically engineered vectors for inserting and expressing foreign genes. The enzymes encoded by TK genes are key kinases in the nucleoside salvage pathway and have signiﬁcant substrate diversity, especially the herpes simplex virus 1 (HSV-1) TK enzyme, which phosphorylates four nucleosides and various nucleoside analogues. Hence, the HSV-1 TK gene is exploited for the treatment of viral infections, as a suicide gene in antitumour therapy, and even for the regulation of stem cell transplantation and treatment of parasitic infection. This review introduces the effects of herpesvirus TK genes on viral virulence and infection in the host and classifies and summarizes the current main application domains and potential uses of these genes. In particular, mechanisms of action, clinical limitations and antiviral and antitumour therapy development strategies are discussed.